SISTEM PENDUKUNG KEPUTUSAN PERPANJANGAN KONTRAK KERJA PEGAWAI TIDAK TETAP (PTT) MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) PADA MPR-RI - Widyawati Widyawati; Ahmad Surahmat; Muhamad Oki Astrabuwono; Syarifah Firyall (Journal of Innovation And Future Technology (IFTECH), 2023)
The MPR-RI is a legislative institution that was established on March 8, 1965, through the Decree of the President of the Republic of Indonesia Number 48/1965. In carrying out its duties, the MPR-RI is assisted by the General Secretariat of the MPR-RI which is a government agency under the auspices of the MPR-RI. The General Secretariat of the MPR-RI has the task of providing administrative support and expertise for the smooth implementation of the MPR-RI's powers and duties. The large number of PTTs working in the General Secretariat of the MPR-RI makes it difficult for the agency to determine the PTT contract extension because it still uses subjective judgments or is based on personal opinion. An assessment like this is certainly very inefficient because it does not have a standard assessment. So an SPK is needed for PTT performance evaluation, the problem-solving method used is the Simple Multi-Attribute Rating Technique (SMART), while the system development tools used are the waterfall model and the Unified Modeling Language (UML) as a system design tool. The result of this research is a website-based decision support system for determining PTT employment contracts.